Approaches to solve the problem of truancy among secondary school students in Kuala Terengganu, Malaysia - Sadiq Ibrahim, Mijinyawa; Norsuhaily, Abu Bakar; Auwalu Shuaibu, Muhammad (2015)
This study examines approaches to solve the problem of truancy among secondary school students in Kuala Terengganu, Malaysia. The study investigated school-based interventions, role of teachers and role of parent teachers’ association in solving truancy. Descriptive survey research design was used where selfadministered questionnaires wereg iven to 100 teachers and 100 parents in five selected secondary schools within Kuala Terengganu district. The schools include:Sekolah Menengah Kebangsaan Kompleks Gong Badak, Sekolah Menengah Kebangsaan Ibrahim Fikri, Sekolah Menengah Agama Khairiah, Sekolah Menengah Kebangsaan Mengabang Telipot, and Sekolah Menengah Kebangsaan Bukit Besar. The data obtained was analyzed using the Statistical Package for Social Sciences (SPSS) version 19.0. Descriptive statistics was used to determine the mean, frequency, percentages and standard deviation of the respondents. The findings of the study indicated that school-based interventions have a positive impact in solving truancy. Role of teachers was also found to have a significant impact in solving truancy. However, based on the result, role of parent teachers’ association was significant in solving the problem of students’ truants’ behaviour. Finally, recommendations were given to school administrators, teachers and parents.